2011
DOI: 10.1111/j.1475-679x.2011.00421.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Financial Incentives in Balanced Scorecard-Based Performance Evaluations: Correcting Mood Congruency Biases

Abstract: Moods are low-intensity affective states that individuals bring to a decision, and may be especially important when the balanced scorecard (BSC) is used for performance evaluation purposes. We propose that financial incentives can motivate decision-makers to correct mood congruency biases, in which judgments and decisions are consistent with moods. In experiment 1, participants rated the performance of one division manager based on two accounting measures and another manager based on a 16-measure BSC; there we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 67 publications
0
35
0
Order By: Relevance
“…This literature has found that subjective weighting processes are affected by intentional and unintentional biases. For example, studies have found evidence of favoritism (Ittner et al 2003), common measure bias Salterio 2000, Libby et al 2004), financial measure bias (Cardinaels and van Veen-Dirks 2010, Johnson et al 2014), outcome effects (Long et al 2015) and mood bias (Ding and Beaulieu 2011). However, with the exception of Bol et al (2016), no other study has looked at the leniency or compression of overall ratings that are the outcome of subjective weighting processes.…”
Section: Introductionmentioning
confidence: 99%
“…This literature has found that subjective weighting processes are affected by intentional and unintentional biases. For example, studies have found evidence of favoritism (Ittner et al 2003), common measure bias Salterio 2000, Libby et al 2004), financial measure bias (Cardinaels and van Veen-Dirks 2010, Johnson et al 2014), outcome effects (Long et al 2015) and mood bias (Ding and Beaulieu 2011). However, with the exception of Bol et al (2016), no other study has looked at the leniency or compression of overall ratings that are the outcome of subjective weighting processes.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies examine the effects of information management in the context of the balanced scorecard (Lipe & Salterio, 2000;Itner, Larcker, & Meyer;Banker, Chang, and Pizzini, 2004;Ding & Beaulieu, 2011). These studies tend to view the information's management processes such as subjectivity, the mood difference, as well as an individual's cognitive effort.…”
Section: Human Information Processing and Balanced Scorecardmentioning
confidence: 99%
“…Overload Ding and Beaulieu (2011) argue that the information generated from the use of the balanced scorecard is classified as an information overload. Referring to the description and Mengis and Eppler (2004), we could conclude that the information generated by the balanced scorecard will positively affect the performance of decision-making, as well as the quality of the decision, until at a certain point, the information provided will degrade the accuracy of the decision-making.…”
Section: Balanced Scorecard and Informationmentioning
confidence: 99%
See 2 more Smart Citations